Assessing the Quality Improvement of Wool Fabric Using Protease Enzyme - . Pooja; Ekta Sharma (Innovations in Science and Technology Vol. 8, 2022)
The present study was undertaken to find the effect of Protease enzyme treatment on wool fabric. Protease enzyme was used for enzyme treatment using five different concentrations (1.0, 2.0, 3.0, 4.0 and 5.0 gm/lt.).The control, scoured and enzyme treated samples were tested for physical properties including hand of the fabric, weight loss, Scanning Electron Microscope (SCM) test, absorbency, pilling, tensile strength, and fabric drape with the help of textile testing equipments named as pilling tester, tensile strength tester, drape meter, crockmeter, perspirometer, SCM Zeiss EVO 50,pH meter, etc. To test the effect of enzymatic degumming on wool fabric dyeability, all samples were dyed with acid dye. Various colorfastness features, such as light, washing, crocking, and perspiration, were tested on the dyed materials. Untreated wool fibre had a fair handle, no absorbency (60 sec), and rough and sharp scales on the surface of the fibre, but after enzyme treatment with various concentrations, wool fabric improved in softness, weight loss (6.31 percent), improved surface scales (smoother), improved absorbency (minimum 45 sec), and drapability. All of the physical and colorfastness qualities of wool cloth improved after treatment with protease enzyme. The 4.0 g/l. concentration of protease enzyme was found to be the best of all the concentrations tested.